Non-judicial remedies and EU administration : protection of rights versus preservation of autonomy - Chirulli, Paola; De Lucia, Luca (Abingdon, Oxon ; New York, NY : Routledge ; [Turin, Italy] : G. Giappichelli Editore, 2021)
"The increasing number of executive tasks assigned to EU institutions and agencies has resulted in an increase in the demand for justice that can no longer be satisfied by the courts alone. This has led to the development of a wide range of administrative remedies that have become a central part of the EU administrative justice system. This book examines the important theoretical and practical issues raised by this phenomenon. The work focuses on five administrative remedies: internal review; administrative review before the Commission of decisions of executive and decentralised agencies; administrative review before boards of appeal of decisions of decentralised agencies; and complaints before the EU Ombudsman and before the EU Data Protection Supervisor. The research rests on the idea that there is a complex, and at times ambivalent, relationship between administrative remedies and the varying degrees of autonomy of EU institutions and bodies, offices and agencies. The work draws on legislation and case law, as well as the internal rules of executive bodies, administrative practices and specific case law, data and statistics. This empirical approach helps to unveil the true dynamics present within these procedures and demonstrates that whilst administrative remedies may improve the relationship between individuals and the EU administration, their interplay with administrative autonomy might lead to a risk of fragmentation and incoherence in the EU administrative justice system"--
Administrative remedies and the autonomy of EU administrations -- Internal review -- Appeals to the Commission against decisions of EU agencies -- Administrative review before the EU Agencies' Boards of Appeal -- Complaints to the European ombudsman -- Administrative remedies and personal data processing -- Administrative remedies : accountability, transformative tensions and the need for constitutionalisation.
OCLC-licensed vendor bibliographic record.
Keywords: European Ombudsman; Administrative remedies -- European Union countries; Judicial review of administrative acts -- European Union countries; Administrative procedure -- European Union countries; LAW / General; LAW / Administrative Law & Regulatory Practice; LAW / Alternative Dispute Resolution